2012
DOI: 10.1016/j.jand.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Adolescents' and Their Friends' Eating Behaviors: Breakfast, Fruit, Vegetable, Whole-Grain, and Dairy Intake

Abstract: The purpose of this study was to examine associations between adolescents’ and friends’ healthy eating behaviors, specifically breakfast, fruit, vegetable, whole grain and dairy food intake as reported by both adolescents and their friends. Data for this study were drawn from EAT-2010 (Eating and Activity among Teens), a population-based study examining multi-level factors of eating, physical activity, and weight-related outcomes among adolescents (80% racial/ethnic minority) in Minneapolis/St. Paul, Minnesota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 38 publications
3
90
0
10
Order By: Relevance
“…Previous research has also found correlations between adolescents' and their friends' eating behaviour (Bruening et al, 2012) suggesting that friends influence each other (Ball, Jeffery, Abbott, McNaughton, & Crawford, 2010;Salvy, de la Haye, Bowker, & Hermans, 2012) and/or conform to common norms (Stead, McDermott, MacKintosh, & Adamson, 2011). It has also been found that friends influence healthy eating negatively (Fitzgerald et al, 2013) by sometimes encouraging adolescents to consume unhealthy foods (Croll, Neumark-Sztainer, & Story, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Previous research has also found correlations between adolescents' and their friends' eating behaviour (Bruening et al, 2012) suggesting that friends influence each other (Ball, Jeffery, Abbott, McNaughton, & Crawford, 2010;Salvy, de la Haye, Bowker, & Hermans, 2012) and/or conform to common norms (Stead, McDermott, MacKintosh, & Adamson, 2011). It has also been found that friends influence healthy eating negatively (Fitzgerald et al, 2013) by sometimes encouraging adolescents to consume unhealthy foods (Croll, Neumark-Sztainer, & Story, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…(21)(22)(23) . Ali et al (22) encontraron en su estudio una asociación positiva entre el individuo y sus amigos en relación a la frecuentación de restaurantes de comida rápida al igual que De la Haye et al (21) , encontraron en esta misma línea, correlación significativa entre el consumo de snacks y comida rápida.…”
Section: Discusión Las Relaciones Sociales Y Su Influencia En La Ingeunclassified
“…Ali et al (22) encontraron en su estudio una asociación positiva entre el individuo y sus amigos en relación a la frecuentación de restaurantes de comida rápida al igual que De la Haye et al (21) , encontraron en esta misma línea, correlación significativa entre el consumo de snacks y comida rápida. Bruening et al (23) clasificaron la amistad como "grupo de amigos" y "mejores amigos" viendo que podría haber diferentes influencias en función de la intensidad del lazo de unión. Efectivamente se encontró asociación significativa entre el grupo de "mejores amigos" y los adolescentes en cuanto a la ingesta del desayuno, de cereales de grano entero, de productos lácteos y en el consumo de verduras, aunque reconoce poca significancia o más bien nula si nos referimos a las frutas.…”
Section: Discusión Las Relaciones Sociales Y Su Influencia En La Ingeunclassified
See 1 more Smart Citation
“…Pengaruh teman sebaya secara signifikan berasosiasi positif dengan asupan buah dan sayur [20,32,33]. Ketersediaan buah dan sayur di rumah juga berasosiasi dengan asupan buah dan sayur.…”
unclassified